The Subsistence and Foodways Transition during the Neolithization Process. Glimpses from a Contextualized Dental Perspective - Bocquentin, Fanny; Chamel, Berenice; Anton, Marie; Noûs, Camille (Food & History, 2021)
Abstract Dental pathologies constitute an important topic for the discussion of subsistence and foodways, especially during periods of major shifts in dietary behaviour. On the eve of the Neolithization process in the Levant, the Natufian period (13000-9500 cal. BC) bears witnesses to a new way of procuring food associated with a decrease in group mobility. New foodstuffs appeared with plant production and husbandry throughout the Early Neolithic period (9500-6400 cal. BC). This article describes both specific and non-specific oral pathologies linked to diet (carious lesions, antemortem tooth loss, abscesses, alveolar resorption) and stress indicators such as Linear Enamel Hypoplasia among Natufian and Neolithic populations based on a huge corpus (over 8,600 teeth) of well contextualized samples that were recorded by the authors following the same procedures. Quantitative and qualitative information were analysed for 24 sites throughout the Levant, attributed to different periods and located in different ecosystems. The results demonstrate a clear increase in caries and associated diseases during the Neolithization process. This was first a gradual process that began as early as the Late/Final Natufian. The linear process was broken by the seventh millennium at which time new behaviours seem to have been introduced resulting in a new pathological pattern. The major changes at this time are observed in Mediterranean contexts where pottery is not yet attested. High biological stress, linked to socioeconomic level or infectious disease, is demonstrated in parallel. Over time, diet seems more and more gendered but less specifically associated with age groups. Abstract Les pathologies dentaires constituent un aspect important de la discussion sur la subsistance et les comportements alimentaires, notamment au moment de transitions alimentaires radicales. À la veille du processus de néolithisation au Levant, la période natoufienne (13000-9500 cal. BC) témoigne d’un nouveau mode d’approvisionnement associé à une diminution de la mobilité des groupes. De nouvelles denrées alimentaires apparaissent avec la production de plantes et l’élevage tout au long du Néolithique ancien (9500-6400 cal. BC). Cet article décrit les pathologies buccales spécifiques et non spécifiques liées à l’alimentation (lésions carieuses, pertes antemortem, abcès, résorptions alvéolaires) et les indicateurs de stress tels que l’hypoplasie linéaire de l’émail dentaire chez les populations du Natoufien et du Néolithique à partir d’un vaste corpus (plus de 8 600 dents) provenant de corpus bien contextualisés et qui ont été enregistrés par les présents auteurs selon les mêmes procédures. Les données quantitatives et qualitatives ont été analysées pour 24 sites à travers le Levant, attribués à différentes périodes et situés dans différents écosystèmes. Les résultats démontrent une nette augmentation des caries et des maladies associées au cours du processus de néolithisation. Il s’agit d’abord d’un processus graduel qui se met en place dès le Natoufien récent/final. Par la suite, le processus linéaire est rompu au 7e millénaire, période à laquelle de nouveaux comportements alimentaires semblent avoir été introduits dans la mesure où un nouveau schéma pathologique domine. Ces changements majeurs sont observés dans des contextes méditerranéens où la céramique n’est pas encore attestée. Un stress biologique élevé, lié au niveau socio-économique ou aux maladies infectieuses, est démontré en parallèle. Au fil du temps, l’alimentation semble de plus en plus sexuée mais moins spécifiquement associée aux groupes d’âge.